Photodegradation of Methylene Blue Using ZnO/Perlite under Ultraviolet Light - Burhanudin; Setyaningtyas, Tien; Riyani, Kapti (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2024)
The disposal of waste in the continuously growing industries leads to pollution caused by pollutants. One of them is liquid waste originating from the textile industry, which contains toxic coloring agents such as methylene blue that are difficult to decompose in the environment. Therefore, an effort is needed to tackle this issue using photocatalysis. A frequently used photocatalyst material is a semiconductor metal oxide like ZnO. However, ZnO semiconductors still have limitations in their applications. To overcome these limitations, ZnO catalysts will be modified with a supporting material like perlite, which is a lightweight and porous material. This study aims to examine the effectiveness of ZnO/Perlite in degrading methylene blue. The ZnO/Perlite composite with a 20% composition shows the highest photocatalytic activity compared to the ZnO/Perlite composites with 10% and 30% compositions. The optimum condition for ZnO/Perlite 20% in degrading methylene blue is achieved with a mass of 0.3 grams, at pH 11, with 2 hours of stirring under ultraviolet light irradiation, resulting in a photocatalytic activity of 47.59% and a combined adsorption and photocatalytic activity of 78.1%.